2009
DOI: 10.1258/acb.2009.008228
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of causes of haemolysis during venepuncture: tourniquet time should be kept to a minimum

Abstract: Background: Haemolysis is defined as the release of cellular components of erythrocytes and other blood cells into the extracellular space of blood. These cellular components can cause interference in laboratory measurements, potassium being a commonly measured analyte to be affected. A number of factors have been implicated in the aetiology of haemolysis. We undertook this study to enable us to identify and hence rectify causes of haemolysis in samples from patients on acute medical and surgical wards. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 5 publications
0
25
1
2
Order By: Relevance
“…Other factors increasing haemolysis in samples, such as tourniquet time, number of attempts at venepuncture and methods of sampling have previously been shown to be related to increased haemolysis rates. 6 In our study, the use of cannula is demonstrated as something that needs to be considered further as a major cause of heamolysis in samples collected in the Emergency Department.…”
Section: Discussionmentioning
confidence: 77%
“…Other factors increasing haemolysis in samples, such as tourniquet time, number of attempts at venepuncture and methods of sampling have previously been shown to be related to increased haemolysis rates. 6 In our study, the use of cannula is demonstrated as something that needs to be considered further as a major cause of heamolysis in samples collected in the Emergency Department.…”
Section: Discussionmentioning
confidence: 77%
“…A study analysing prevalence of haemolysis in blood samples taken from adolescents (mean age of 17.3 years) (Vissers et al, 2008) found that 0.8% of samples were strongly (grade 2) haemolysed and concluded that more research into strategies for reducing haemolysis when taking samples is needed. A study by Saleem et al (2009) showed that the duration with which the tourniquet is applied during blood sampling was the most significant factor in causing haemolysis, with times of over one minute resulting in an almost 20 times greater probability. Similar observations were published by Blazys (1999) and Becan-McBride (1999).…”
Section: Venepuncture Procedures Analysismentioning
confidence: 99%
“…These values were estimated based on the findings from Saleem et al (2009), Blazys (1999 and Becan-McBride (1999). The probability of laboratory rejection due to the other causes, such as the insufficient sample quantity, contamination and incorrect labelling, was estimated based on the data from Jones et al (1997) to be 0.0014.…”
Section: Task Modelsmentioning
confidence: 99%
“…그러나 실제 문헌에서 제시된 채혈관련 검체의 용혈 발생률은 6.5% (Saleem, Mani, Chadwick, Creanor, & Ayling, 2009), 12.8% (Dugan, Leech, Speroni, & Corriher, 2005). 19.8% (Ong, Chan, & Lim, 2008), 심지어 32% (Grant, 2003) (Dugan et al, 2005;Grant, 2003;Kennedy et al, 1996), 토니켓 적용시간 (Saleem et al, 2009).…”
Section: 진단검사에 대한 정도관리를 하고 있는 미국의 임상병리사회에unclassified
“…그러나 실제 문헌에서 제시된 채혈관련 검체의 용혈 발생률은 6.5% (Saleem, Mani, Chadwick, Creanor, & Ayling, 2009), 12.8% (Dugan, Leech, Speroni, & Corriher, 2005). 19.8% (Ong, Chan, & Lim, 2008), 심지어 32% (Grant, 2003) (Dugan et al, 2005;Grant, 2003;Kennedy et al, 1996), 토니켓 적용시간 (Saleem et al, 2009). 채혈자의 숙련도 (Lowe et al, 2008), 채혈 시 사용되는 주사바늘의 크기 (Dugan et al;Kennedy et al, 1996), 혈액이 수집되는 채혈관의 크기 (Cox et al, 2004;Dugan et al), 채혈시도 횟수, 진단명 및 채혈부위 (Dugan et al), 검체 이송방법 (Fang, Fang, Chung, & Chien, 2008 채혈로 인한 용혈관련 문헌을 살펴보면, 외국의 경우는 용혈발생 에 대한 실태조사 (Fernandes, Walker, Price, Marsden, & Haley, 1997;Grant, 2003), 용혈발생 영향요인 (Dugan et al, 2005), 채혈방법에 따른 용혈 비교 (Cox et al, 2004;Grant;Kennedy et al, 1996;Lowe et al, …”
Section: 진단검사에 대한 정도관리를 하고 있는 미국의 임상병리사회에unclassified